Enhanced Pd/a‐WO3/VO2 Hydrogen Gas Sensor Based on VO2 Phase Transition Layer. Issue 12 (26th October 2022) - Li, Bowen; Wang, Zhaowu; Zhao, Shanguang; Hu, Changlong; Li, Liang; Liu, Meiling; Zhu, Jinglin; Zhou, Ting; Zhang, Guobin; Jiang, Jun; Zou, Chongwen
Abstract: The utilization of clean hydrogen energy is becoming more feasible for the sustainable development of this society. Considering the safety issues in the hydrogen production, storage, and utilization, a sensitive hydrogen sensor for reliable detection is essential and highly important. Though various gas sensor devices are developed based on tin oxide, tungsten trioxide, or other oxides, the relatively high working temperature, unsatisfactory response time, and detection limitation still affect the extensive applications. In the current study, an amorphous tungsten trioxide (a‐WO3 ) layer is deposited on a phase‐change vanadium dioxide film to fabricate a phase transition controlled Pd/a‐WO3 /VO2 hydrogen sensor for hydrogen detection. Results show that both the response time and sensitivity of the hydrogen sensor are improved greatly if increasing the working temperature over the transition temperature of VO2 . Theoretical calculations also reveal that the charge transfer at VO2 /a‐WO3 interface becomes more pronounced once the VO2 layer transforms to the metal state, which will affect the migration barrier of H atoms in a‐WO3 layer and thus improve the sensor performance. The current study not only realizes a hydrogen sensor with ultrahigh performance based on VO2 layer, but also provides some clues for designing other gas sensors with phase‐change material. Abstract : Considering the safety issues in the hydrogen production, storage, and utilization, a sensitive hydrogen sensor for reliable detection is essential and highly important. Here, a high sensitive Pd/a‐WO3 /VO2 hydrogen sensor based on VO2 phase transition layer is achieved. This phase transition enhanced hydrogen gas sensor suggests a novel strategy for other gas sensors fabrications in the future.